The Dog Who Had Kittens - Robertus, Polly M.; Stevens, Janet (New York : Holiday House, 1991)
Baxter the basset hound feels jealous and then protective of Eloise the cat's kittens, but one day the kittens disappear, and he must adjust and make peace with Eloise .
"This story first appeared in Cricket, the magazine for children, March 1988, volume 15, number 7"--Verso t.p.
Keywords: Dogs -- Fiction; Cats -- Fiction